Адвокатура України в умовах воєнного стану - Бандурка, С. С.; Bandurka, S. S. (Наше право. - 2022. - № 2. - С. 25-30, 2022)
В статті розглянуті окремі питання діяльності адвокатури України в період воєнного стану. Роль адвокатури в умовах війни зростає у зв’язку із значним збільшенням постраждалих від військових дій, обстрілів, бомбардувань мирного населення, втрат рідних і близьких людей. Адвокатура керується нормами Закону України «Про адвокатуру та адвокатську діяльність», але має враховувати можливості обмеження, обумовлені введенням воєнного стану на території України. Висвітлені ті обставини, за яких адвокати мають функціонувати під час воєнного стану і з якими в мирний час вони не стикалася. Пропонується у поствоєнний час удосконалити законодавство України про адвокатуру для того, щоб вона ефективно регулювала діяльність адвокатів в різних ситуаціях, в тому числі і воєнних, зберігаючи головний принцип функціонування адвокатури – незалежність.

The article considers some issues of functioning of Ukrainian attorneys during the martial law. The role of the legal profession in wartime is growing due to the signifi cant increase of casualties from hostilities, shelling, civilian bombings, and the loss of close ones. Functioning of Ukrainian attorneys is guided by the provisions of the Law of Ukraine «On Advocacy and Functioning of Ukrainian Attorneys « but must also take into account the possibility of restrictions due to the installment of the martial law in Ukraine. Circumstances under which attorneys function during the martial law and which they have not encountered in peacetime are highlighted in the article. It is suggested to improve the legislation of Ukraine on the functioning of attorneys during the postwar period so that it effectively regulates activities of the attorneys in different situations, while maintaining the main principle of the advocacy - Independence.

В статье рассмотрены отдельные вопросы деятельности адвокатуры Украины в период военного положения. Роль адвокатуры в условиях войны растет в связи со значительным увеличением пострадавших от военных действий, обстрелов, бомбардировок мирного населения, потерь родных и близких людей. Адвокатура руководствуется нормами Закона Украины «Об адвокатуре и адвокатской деятельности», но должна учитывать возможности ограничения, обусловлены введением военного положения на территории Украины. Освещены те обстоятельства, при которых адвокаты должны функционировать во время военного положения и с которыми в мирное время они не сталкивались. Предлагается в послевоенное время усовершенствовать законодательство Украины об адвокатуре.
Keywords: адвокатура; Україна; адвокати; воєнний стан; права і свободи; військові дії; злочини; потерпілі; правова допомога; advocacy; Ukraine; attorneys; martial law; rights and freedoms; military actions; crimes; victims; legal aid; Украина; адвокаты; военное положение; права и свободы; военные действия; преступления; потерпевшие; правовая помощь